Cost estimation for post abrasive waterjet cutting on customized jigsaw rubber mats - Thongkaew, Kunlapat; Naemsai, Thanwit; Mustafa, Zaleha (Penerbit UTeM, 2023)
Rubber items are usually made through molding, which requires a large manufacturing capacity to obtain economies of scale. Post-cutting enables rubber goods to be customized without an entirely new molding process. Abrasive waterjet (AWJ) cutting is currently used to cut rubber and other materials, but limited is known about its costs. In order to evaluate the feasibility of post-AWJ cutting technology for enhancing the value of rubber products, this study aims to estimate the post-abrasive waterjet cutting required for modifying plain rubber mats to customized jigsaw rubber mats. These distinctive goods can result in value-added products that increase manufacturers' revenue and competition. It was determined how much the production of rubber mats and the post-AWJ cutting operation would cost. The variables affecting the AWJ cutting cost and the cost of producing rubber mats were examined. After that, a case study of making jigsaw rubber mats was used to calculate the unit cost of the rubber mat and the post-AWJ cutting. It was discovered that the cutting quality of the AWJ on the rubber mats was also acceptable. The additional cost for post-AWJ cutting is accounted for simply 2.97% of the overall production costs. As a result, post-AWJ cutting can be used to create jigsaw rubber mats, and it is appropriate for customized items that manufacturers can market for 50% more than a plain rubber mat